Integrating indigenous and Islamic perspectives in the field of psychology - Abdul Rahman, Shukran (2019)
Background: Psychology and Psychology Education have been based on mainstream or general Psychology without neglecting the importance of indigenous psychology. The latter is necessary because the former originated and reflected the nature, culture or characteristics of people in other places which are not appropriate to be generalized to other settings. An essential perspective in indigenous Psychology is the presence of values subscribed by people in a population, including the religious-based values. Objective: This paper discusses the importance of indigenous psychology, highlighting the need to integrate it with the Islamic perspective. It also highlights the ways Muslim scholars in various localities discussed the nature of human characteristics, from Islamic and indigenous perspectives combined. Source of Information: Review of literature on early scholars who discussed the nature of human, the methods to study human, and the importance of studying human characteristics. Findings: There are various notions of Islamic perspective which have been found in the work of Muslim scholars when they discussed the nature of human being. Three essential notions have been identified, namely (a) the axiological notion (underlying principles which govern their approaches to study human characteristics); (b) the epistemological notion (the approaches in studying human nature) and (c) ontological notion (the scopes of studies on human nature). Significance: The input discussed in this paper could provide alternative description to the general Psychology on human nature. It may also shed light on the ways to derive Psychology knowledge from Islamic sources and integrate it with indigenous values.